Participatory Action Research with 'Minority Communities' and the Complexities of Emancipatory Tensions: Intersectionality and cultural affinity. (December 2014) - Sallah, Momodou
Conducting research with communities constructed as the 'other' from a purely positivist paradigm can often be replete with colossal flaws with enormous potential to oppress the researched – especially minority communities in this case. This article presents an analysis of the cultural and experiential affinity experiences of the author towards a constructivist approach where the research process is emancipatory and the ultimate goal of engagement is for both the researcher and the researched to become co-producers of knowledge. The multidimensional identities of some 'minority communities' and their intersectionality are also discussed. This includes an exploration of this author's identity as a visible member of minority groups and the resulting cultural affinity that imbues his research as well as the participatory nature of his approach that seeks to liberate. The article will also highlight methodological implications of this author's empiric work, complemented by lessons drawn from recent research projects conducted with 'minorities' in different parts of the UK to illuminate methodological complexities and illustrate anti-oppressive practice with 'minority communities'. This article is framed around the four theoretical constructs of Intersectionality; Participatory Action Research; Cultural Affinity/Experiential Affinity; and Freire's transformative education pedagogy.